2014
DOI: 10.1177/1049732314546754
|View full text |Cite
|
Sign up to set email alerts
|

Translating Advances in Cardiogenetics Into Effective Clinical Practice

Abstract: In this article we describe a qualitative research study in which we explored individuals’ subjective experiences of both genetic testing and cardiogenetic disorders. Using a grounded theory approach, we coded and analyzed interview and focus group transcripts from 50 participants. We found that just under half of the participants who received their diagnosis during the study reported difficulty understanding information about both the purpose of genetic testing and their cardiac disease. A high level of anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…From the standpoint of the general public, although some individuals may feel comfortable in using genetics-related terms in a conversation, their understanding of the underlying scientific concepts can remain relatively limited (Lanie et al, 2004; Rogers et al, 2018; Silverstein et al, 2014). Furthermore, as the public’s understanding of genetics mainly revolves around issues of heredity (Condit, 2010; Daack-Hirsch, Shah, & Cady, 2018; Lee et al, 2017; Navarro de Souza, Groleau, Loiselle, Foulkes, & Wong, 2014; Rogers et al, 2018), the relationship between genes and the likelihood or not of responding well to a given medication is a subject that is still unfamiliar to patients (Haga et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…From the standpoint of the general public, although some individuals may feel comfortable in using genetics-related terms in a conversation, their understanding of the underlying scientific concepts can remain relatively limited (Lanie et al, 2004; Rogers et al, 2018; Silverstein et al, 2014). Furthermore, as the public’s understanding of genetics mainly revolves around issues of heredity (Condit, 2010; Daack-Hirsch, Shah, & Cady, 2018; Lee et al, 2017; Navarro de Souza, Groleau, Loiselle, Foulkes, & Wong, 2014; Rogers et al, 2018), the relationship between genes and the likelihood or not of responding well to a given medication is a subject that is still unfamiliar to patients (Haga et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…163 Also, a substantial number of patients find information about both the purpose of genetic testing and their cardiac disease difficult to understand. A high level of anxiety about genetic testing and cardiac symptoms may lead to distress and confusion, 164 whereas a positive genetic result by itself may not necessarily impact patient well-being negatively. 165 Thus, clear communication of arrhythmia-specific risk stratification is also important to help temper the psychological response.…”
Section: Patients' Experiences Of Living With Ventricular Arrhythmiasmentioning
confidence: 99%
“…One of the themes that evolved during this analysis was the anxiety associated with finding out test results. Within this theme, one of the repeating ideas was worry about the next generation (Silverstein et al, Unpublished Manuscript). For the present study, we extracted comments and identified parental perspectives specifically relevant to reproductive decision making.…”
Section: Methodsmentioning
confidence: 99%